The holiday - Block, Bruce A.; Meyers, Nancy; Diaz, Cameron; Winslet, Kate.; Law, Jude, 1972-; Black, Jack, 1969-; Wallach, Eli, 1915-; Burns, Edward, 1968-; Sewell, Rufus, 1967-; Englefield, Miffy; Pritchard, Emma.; Parish, Sarah; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2007)
Amanda lives in Los Angeles and Iris lives in Surrey, England. They both come upon a website that advocates home exchange and the two swap houses for two weeks at Christmas.
Title from disc surface.
Originally released as a motion picture in 2006.
Director of photography, Dean Cundey ; editor, Joe Hutshing ; original music, Hans Zimmer ; costume designer, Marlene Stewart ; production designer, Jon Hutman.
Cameron Diaz, Kate Winslet, Jude Law, Jack Black, Eli Wallach, Edward Burns, Rufus Sewell, Miffy Englefield, Emma Pritchard, Sarah Parish, Shannyn Sossamon, Bill Macy.
MPAA rating: PG-13; for sexual content and some strong language.
DVD; Dolby digital 5.1.
Keywords: Home exchanging -- California -- Los Angeles -- Drama; Home exchanging -- England -- Surrey -- Drama; Women -- California -- Los Angeles -- Drama; Women -- England -- Surrey -- Drama; Women -- Sexual behavior -- Drama; Man-woman relationships -- Drama; Romantic comedy films; Feature films; Films for the hearing impaired; Love stories; Comedy films